“Should I Submit a Blank Assignment?!!”: The Effect of Machine Translation on the Writing Process and Performance among Thai EFL Students with Low English Proficiency - Namfah, Nattharmma (LEARN Journal: Language Education and Acquisition Research Network, 2024)
This study explores how machine translation (MT) influences the English writing process and performance of 29 9th-grade EFL students with limited English proficiency. Over 10 writing tasks conducted during the semester, participants had varied accessibility to MT. The research compared their performance when MT was permitted versus when it was not, assessed through evaluations of their assignments. Employing the technology acceptance model (TAM) as the analytical framework, the study utilized teacher notes and retrospective think-aloud interviews to glean insights into participants' MT usage and the influencing factors. Results indicate that MT usage significantly enhances final writing outcomes. A closer examination revealed that participants with MT access predominantly used writing strategies during the planning phase but evaded the drafting and reviewing processes. They tended to compose assignments in their native language (L1), which was Thai, and directly translate them into English when utilizing MT. Conversely, when MT was unavailable, many participants abandoned the tasks entirely. Factors like perceived limited linguistic competence, disengagement from the writing process, ease of MT accessibility, perceived effectiveness of MT, and peer influence were critical determinants in their MT usage decisions. This study emphasizes the need for guiding effective integration of MT as a supportive tool, discouraging over-reliance.